Selection of suitable reference genes for gene expression studies in myxosporean (Myxozoa, Cnidaria) parasites - Kosakyan, Anush; Alama-Bermejo, Gema; Bartošová-Sojková, Pavla; Born-Torrijos, Ana; Šíma, Radek; Nenarokova, Anna; Eszterbauer, Edit; Bartholomew, Jerri; Holzer, Astrid S (Scientific reports, 2019)
Myxozoans (Cnidaria: Myxozoa) are an extremely diversified group of endoparasites some of which are causative agents of serious diseases in fish. New methods involving gene expression studies have emerged over the last years to better understand and control myxozoan diseases. Quantitative RT-PCR is the most extensively used approach for gene expression studies. However, the accuracy of the results depends on the normalization of the data to reference genes. We studied the expression of eight commonly used reference genes, adenosylhomocysteinase (AHC1), beta actin (ACTB), eukaryotic translation elongation factor 2 (EF2), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), hypoxanthine-guanine phosphoribosyltransferase 1 (HPRT1), DNA-directed RNA polymerase II (RPB2), 18S ribosomal RNA (18S), 28S ribosomal RNA (28S) across different developmental stages of three myxozoan species, Sphaerospora molnari, Myxobolus cerebralis and Ceratonova shasta, representing the three major myxozoan linages from the largest class Myxosporea. The stable reference genes were identified using four algorithms: geNorm, NormFinder, Bestkeeper and ΔCq method. Additionally, we analyzed transcriptomic data from S. molnari proliferative and spore-forming stages to compare the relative amount of expressed transcripts with the most stable reference genes suggested by RT-qPCR. Our results revealed that GAPDH and EF2 are the most uniformly expressed genes across the different developmental stages of the studied myxozoan species.
Keywords: Parasites; algoritmy; Animals; RNA, Messenger; transkriptom; regulace genové exprese; Reference Standards; Oncorhynchus mykiss; paraziti; zvířata; referenční standardy; Gene Expression Regulation; Transcriptome; messenger RNA; Myxozoa; Algorithms